State-of-the-art of urban traffic management policies and technologies. - Kaparias, I.; Zavitsas, K.; Bell, M. G. H. (My University, 2010)
The report is the second part of the first stage of CONDUITS, whose objective is to establish the state-of-the-art of urban traffic management in Europe and beyond, with a particular focus on Intelligent Transport Systems (ITS). Broadly summarising the results, it can be said that, a wide range of traffic management technologies and policies seems to be used in Europe and worldwide. It is encouraging to see that strategic plans and traffic control centres are generally present in the participating cities, as well as facilities for public transport, ITS technologies and real-time public transport information. In addition, most cities have cycling infrastructure, pedestrian zones and alternative mobility schemes, as well as good policies for weaker population categories, such as the elderly, the jobless and the disabled. While the report has some shortcomings with respect to the reliability of the data provided by the cities, mainly originating from different definitions or from the absence of data all together, it can be considered a fairly good overview of the state-of-the art of urban traffic management. It is planned to make full use of the assembled dataset in the application of the key performance indicators developed in the next stages of CONDUITS.
Keywords: Individualverkehr; Fahrradverkehr; Stadtverkehr; Verkehrsplanung; Radverkehrsplanung; Fahrradinfrastruktur; Radverkehrsförderung; Radverkehrsanlage